Projetopê: a guided free improvisation co-organized through the interactions between human musicians and a digital machine - Schaub, Stéphan; Bonduki, Said (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação Musical, 2025)
In the following contribution we present the overall outline of a musical improvisation environment in which musicians interact with a digital machine endowed with capacities to listen, to memorize, to communicate visual information and to synthesize sounds. The proposal innovates by shifting the focus away from real-time interactions to concentrate on the organization of larger time spans and on the production of a type of guided improvisation situated somewhere between the practice of entirely free improvisation and written, open composition. To achieve this goal, temporal segments are defined and their succession as well as their characteristics dynamically driven by the interactions between the improvisers and the digital machine. The name Projetopê refers both to a subset of these possibilities and to an initial implementation programmed in Max/MSP. The latter presents itself as an “extended score”, materialized on individual computer screens. Over the course of the performance the machine analyzes parameters such as pitch, register, duration and dynamics. It then uses the information to trigger the transitions between sections of the improvisation (thus making their durations variable) as well as to determine the pitches / harmonies it itself projects, usually between – occasionally also during – these same sections.